The Use of Quizizz Media to Increase Students Interest in Learning Science at Primary Schools - Edi Handoko, Sofa Binti Masruroh; Singgih Subiyantoro (Cognitive Development Journal, 2024)
Learning media should be utilized to enhance the quality of education in the digital era. It can inspire and motivate students to engage in the learning process, thereby increasing their interest in learning. This study aims to improve the learning interest of fourth-grade students by using learning media in the form of Quizizz. The research is categorized as Classroom Action Research, with the subjects being 15 fourth-grade students, consisting of 6 girls and 9 boys. Data collection instruments included observation, evaluation tests, and interviews. The Classroom Action Research design was carried out in two cycles, each consisting of the following stages, planning, implementation, observation, and reflection. The results indicate that the use of Quizizz as a learning medium effectively enhances students learning interest. In the first cycle, without the use of the Quizizz application, students learning interest reached 59.64 percent, which is categorized as moderate. In the second cycle, after implementing Quizizz, students learning interest increased to 74.29 percent, placing it in the high category. This improvement demonstrates that the use of interactive learning media such as Quizizz is effective in fostering greater student engagement. Therefore, integrating Quizizz into the learning process is a promising strategy for teachers to enhance students’ interest in learning in the fourth grade.